2020
DOI: 10.1177/0300060519897190
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset androgenetic alopecia in China: a descriptive study of a large outpatient cohort

Abstract: Objective: To describe the clinical features of early-onset androgenetic alopecia (AGA) in a large cohort of Chinese patients. Methods: This descriptive study recruited consecutive patients seeking medical treatment for AGA between 1 January 2013 and 30 November 2018. Patients were included in the study if they reported being 35 years old at AGA onset and if their pattern of hair loss was documented with photographs. The age of onset, sex, body mass index (BMI), BAsic and SPecific classification of hair loss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Conversely, other studies have denied this relationship. Ding et al reported the epidemiologic data regarding AGA in Chinese young adults which No association was found between high BMI (>25 kg/m2) and early-onset AGA [ 13 ]. In consistence, our results also suggested that there was no significant association between BMI and AGA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies have denied this relationship. Ding et al reported the epidemiologic data regarding AGA in Chinese young adults which No association was found between high BMI (>25 kg/m2) and early-onset AGA [ 13 ]. In consistence, our results also suggested that there was no significant association between BMI and AGA.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Fortes et al also showed that the combination of overweight and smoking is associated with an increased severity of androgenetic alopecia [ 12 ]. However, there are also other studies demonstrating that there was no significant association between these cardiovascular risk factors (such as hypertension, smoking, BMI) and AGA [ 10 , 13 ]. For college students, it is quite rare for them to have hypertension or other cardiovascular diseases at their age.…”
Section: Introductionmentioning
confidence: 99%
“…AGA, or male pattern baldness affects 30–50% men at the age of 50, and 80% men at the age of 80 (Fig. 2 A; Hamilton 1951 ; Wang et al 2010 ; Ding et al 2020 ). Thus it is a common trait in the population.…”
Section: Dysregulation Of Hair Regeneration In Agamentioning
confidence: 99%
“…Alopecia, a common disorder occurring worldwide, characterized by hair loss, can be caused by multiple factors, such as heredity, hormonal disorders, immune inflammation, malnutrition, environmental factors, mental disorders, and aging ( Ho and Shapiro, 2019 ). Androgen alopecia (AGA) is the most common type of alopecia and has become an important medical and social issue due to its high incidence; increasingly young onset age; and associated psychological problems, such as depression, anxiety, and emotional disorders ( Bas et al, 2015 ; Molina-Leyva et al, 2016 ; Katzer et al, 2019 ; Ding et al, 2020 ). Currently, finasteride and minoxidil are the only therapeutic drugs approved by the Food and Drug Administration for AGA treatment ( Chen et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%